Formation of the formate-nitrate electron transport pathway from inactive components in Escherichia coli. - Scott, R H (1976)
When Escherichia coli was grown on medium containing 10 mM tungstate the formation of active formate dehydrogenase, nitrate reductase, and the complete formate-nitrate electron transport pathway was inhibited. Incubation of the tungstate-grown cells with 1 mM molybdate in the presence of chloramphenicol led to the rapid activation of both formate dehydrogenase and nitrate reductase, and, after a considerable lag, the complete electron transport pathway. Protein bands which corresponded to formate dehydrogenase and nitrate reductase were identified on polyacrylamide gels containing Triton X-100 after the activities were released from the membrane fraction and partially purified Cytochrome b1 was associated with the protein band corresponding to formate dehydrogenase but was not found elsewhere on the gels. When a similar fraction was prepared from cells grown on 10 mM tungstate, an inactive band corresponding to formate dehydrogenase was not observed on polyacrylamide gels; rather, a new faster migrating band was present. Cytochrome b1 was not associated with this band nor was it found anywhere else on the gels. This new band disappeared when the tungstate-grown cells were incubated with molybdate in the presence of chloramphenicol. The formate dehydrogenase activity which was formed, as well as a corresponding protein band, appeared at the original position on the gels. Cytochrome b1 was again associated with this band. The protein band which corresponded to nitrate reductase also was severely depressed in the tungstate-grown cells and a new faster migrating band appeared on the polyacrylamide gels. Upon activation of the nitrate reductase by incubation of the cells with molybdate, the new band diminished and protein reappeared at the original position. Most of the nitrate reductase activity which was formed appeared at the original position of nitrate reductase on gels although some was present at the position of the inactive band formed by tungstate-grown cells. Apparently, inactive forms of both formate dehydrogenase and nitrate reductase accumulate during growth on tungstate which are electrophoretically distinct from the active enzymes. Activation by molybdate results in molecular changes which include the reassociation of cytochrome b1 with formate dehydrogenase and restoration of both enzymes to their original electrophoretic mobilities.